PENGUKURAN WAKTU STANDARD OPERATING PROCEDURE DALAM MENINGKATKAN PRODUKTIVITAS KARYAWAN DENGAN ANALISIS SIMULASI DAN CRITICAL PATH METHOD - Wisnubroto, Petrus; Rosyid, Muhammad Abdur (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
A rich organization never warrants its member to get wealthy. It will depend on human resources empowering including floor labors that has strategic position in achie-ving organizations goal. Fluctuations of employee’s productivity performance will hardly controllable if the organization had no standardization of work. One kind of standardiza-tion of work is Standard Operating Procedure (SOP) that contains technical procedure of activity and it parametric measurement. To analyze trend of employee’s performance ti-me, computer simulation will assist to know the tendency of data that so called with com-puter simulation analysis. The result of analysis will be followed by productivity improve-ment method such as Critical Path Method (CPM). Inexistence of SOP in Balai Yasa PT. Kereta Api Yogyakarta (BY YK) will be followed up by making Standardization of work in the term of SOP using work time standard measurement consideration. By using simu-lation analysis approach that resulting very good performance of employee in BY YK. This advantageous indicator gives information ability of production improvement. By u-sing Standardization of work time and implementation of CPM able to reduce 21% of total time in assembling locomotive or approximately 158 minutes. The combination of both method results critical path of locomotive assembly activity starting from activity A, B, C, D, E, F, G, H ,I ,J ,K , L, M , N, O, P, Q, R,S, T, U,V, X, Y.